Pelatihan Digital Marketing Untuk Meningkatkan Pemasaran UMKM Gerabah Di Desa Banyumulek - Sofiati Wardah; Rosyia Wardani; Galuh Ratna Mutia; Syaiful Amri; Zulkarnaen; Sopian Saori; Satriawan; Baiq Desthania Prathama; Hikmah; Putri Reno Kemala sari; Baiq Ertin Helmida (Valid Jurnal Pengabdian, 2025)
The problem faced by pottery craftsmen in Banyumulek Village is the lack of knowledge of business actors in using digital marketing to market their products. The 2018 earthquake and Covid 19 were obstacles and obstacles for craftsmen which caused the lack of enthusiasts and tourists so that they were forced to change professions as agricultural laborers. Lack of promotion is one of the causes so government attention is needed. Therefore, providing training and assistance to Banyumulek Village Pottery MSMEs regarding the use of social media in promoting their products or crafts which are still traditional is expected to help revive the economy of the craftsmen so that they can be recognized by the global community